2014 Cool-Season Forage Variety Recommendations for Florida - Ann R. Blount; Joao M. B. Vendramini; Jose C. B. Dubeux; Md. A. Babar; Kevin E. Kenworthy; Patricio R. Muñoz; Kenneth H. Quesenberry (EDIS)
This revised 4-page fact sheet provides the most up-to-date information on current adapted varieties of cool-season forages. The recommendation of varieties is based on multi-location, multi-year cultivar evaluation experiments that may include trials in Georgia and other states. Table 1 includes information about the planting dates, seeding rates, and other considerations. If you have questions about a particular variety, contact your local UF/IFAS Extension agent for additional information. Written by A. R. Blount, J. M. B. Vendramini, J. C. B. Dubeux, Md A. Babar, K. E. Kenworthy, P. R. Muñoz,and K. H. Quesenberry, and published by the UF Department of Agronomy, September 2014. (UF/IFAS Photo: Josh Wickam)